Implementasi Undang-Undang No. 1 Tahun 2011 terhadap Kondisi Perumahan bagi Masyarakat Berpenghasilan Rendah di Kota Medan - H. Riza Sirait; Rudi Salam Sinaga; Maksum Syahri Lubis (Universitas Medan Area, 2021)
The purpose of this research is to Know and explain the results of the evaluation of the quality of housing conditions for low-income people (MBR) in Medan City, Know and explain the implementation of Law no. 1 of 2011 concerning Housing and Settlement Areas for MBR in Medan City, Knowing and explaining the supporting factors and obstacles to improving the quality of housing conditions for low-income people (MBR) in Medan City. This research is a qualitative design. The research approach is based on phenomenology and the constructivism paradigm in developing science. The results of the research are normatively Law no. 1 of 2011 has been quite effective in accommodating the provision of housing support for low-income families. Implementation of 1 Year 2011, there are still many problems, especially those related to the role and capacity of local governments, both in terms of commitment and funding, so it is necessary to develop derivative regulations related to local governments. There are still weaknesses in housing regulations, among others, related to the current income limit for MBR, which is relatively 35% higher than the average wage / salary income of people in Indonesia, as well as the benchmark for common house prices which are 44% lower in value than the market price in accordance with construction costs on the market.